Camouflage and masking behavior in adult autism - Alaghband-rad, Javad; Hajikarim-Hamedani, Arman; Motamed, Mahtab (Frontiers in Psychiatry, 2023)
Autism Spectrum Disorder (ASD) is characterized by persistent deficits in social communication and social interaction across multiple contexts. Social camouflaging was first shown to be a characteristic of autistic persons, who actively try to disguise and compensate for their autism features in social contexts in an effort to socially blend in better. Recently, an increasing, though still insufficient, number of studies has been conducted on the concept of camouflage; however, different aspect of it, from psychopathology and etiology to its complications and consequences, are not clearly defined. We aimed to systematically review the existing literature on camouflage in autistic adults to describe the correlates of camouflage, motivations for exhibiting camouflage behavior, and the potential impacts of camouflage on the mental health of autistic individuals. We followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) checklist guidelines to conduct a systematic review. The databases of PubMed and Scopus, and PsycInfo were searched for eligible studies. Studies were published between January 1st, 1980, to April 1st, 2022. We included 16 articles, of which four studies were qualitative and 11 were quantitative. One study used a mix method. The assessment tools used for camouflage, the correlates of camouflage including autism severity, gender, age, cognitive profile and neuroanatomical correlates, reasons for camouflage and the impacts of camouflaging behavior on mental health are discussed in this review. In synthesizing the literature, we conclude that camouflage seems to be more common among females who report more autistic symptoms themselves. There may also be some differences between men and women in reasons of exhibiting it and its neuroanatomical correlates. Further research is needed as to why this phenomenon is more prevalent in females with implications for gender related cognitive and neuroanatomical differences. Effects of camouflage on mental health and daily life measures of individuals such as employment, university graduation, relationship, financial status, and quality of life should be studied with more details in future studies.